2018
DOI: 10.1002/hpm.2496
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the effectiveness of reward schemes from 10‐year longitudinal case studies in 2 Italian regions.

Abstract: SummaryBackgroundPay for performance (P4P) programs have been widely analysed in literature, and the results regarding their impact on performance are mixed. Moreover, in the real‐life setting, reward schemes are designed combining multiple elements altogether, yet, it is not clear what happens when they are applied using different combinations.ObjectivesTo provide insights on how P4P programs are influenced by 5 key elements: whom, what, how, how many targets, and how much to reward.MethodsA qualitative longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(136 reference statements)
0
6
0
1
Order By: Relevance
“…The choice of whom should be involved earliest is also important: involving recognised leaders, champions, and influencers can help in engaging other colleagues and collaborators. Other managerial mechanisms can be used to improve this viral effect, such as reputation or the inclusion of PROMs data into the performance evaluation systems .The comparison of performance within a community of professional practice as well as through public disclosure of performance benchmarking can result in improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of whom should be involved earliest is also important: involving recognised leaders, champions, and influencers can help in engaging other colleagues and collaborators. Other managerial mechanisms can be used to improve this viral effect, such as reputation or the inclusion of PROMs data into the performance evaluation systems .The comparison of performance within a community of professional practice as well as through public disclosure of performance benchmarking can result in improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this specific level of data reporting can indicate to managers the variability of performance between wards and services [42]. This internal benchmarking is an important activity for improving the patient experience [23] and reducing internal variation [43][44][45][46]. The comparison of data among homogeneous wards is also very relevant.…”
Section: Level Of Data Aggregation Benchmarking and Timelinessmentioning
confidence: 99%
“…A recent study on collaborative performance management found that seniority, participation in goal setting, and goal salience are factors encouraging interagency collaboration and in particular, goal factors are the most influential variables [16]. In particular, in healthcare organizations the use of salient goal setting is found to be one of the most relevant successful factor of managing performance by objectives [32].…”
Section: Performance Management In Collaborative Settingmentioning
confidence: 99%